In vivo low-dose phase-contrast CT for quantification of functional and anatomical alterations in lungs of an experimental allergic airway disease mouse model - Dullin, Christian; Albers, Jonas; Tagat, Aishwarya; Lorenzon, Andrea; D'Amico, Lorenzo; Chiriotti, Sabina; Sodini, Nicola; Dreossi, Diego; Alves, Frauke; Bergamaschi, Anna; Tromba, Giuliana (Frontiers in Medicine, 2024)
Introduction Synchrotron-based propagation-based imaging (PBI) is ideally suited for lung imaging and has successfully been applied in a variety of in vivo small animal studies. Virtually all these experiments were tailored to achieve extremely high spatial resolution close to the alveolar level while delivering high x-ray doses that would not permit longitudinal studies. However, the main rationale for performing lung imaging studies in vivo in small animal models is the ability to follow disease progression or monitor treatment response in the same animal over time. Thus, an in vivo imaging strategy should ideally allow performing longitudinal studies. Methods Here, we demonstrate our findings of using PBI-based planar and CT imaging with two different detectors—MÖNCH 0.3 direct conversion detector and a complementary metal-oxide-semiconductor (CMOS) detector (Photonics Science)—in an Ovalbumin induced experimental allergic airway disease mouse model in comparison with healthy controls. The mice were imaged free breathing under isoflurane anesthesia. Results At x-ray dose levels below those once used by commercial small animal CT devices at similar spatial resolutions, we were able to resolve structural changes at a pixel size down to 25 μm and demonstrate the reduction in elastic recoil in the asthmatic mice in cinematic planar x-ray imaging with a frame rate of up to 100 fps. Discussion Thus, we believe that our approach will permit longitudinal small animal lung disease studies, closely following the mice over longer time spans.